Singapore Undercovered - Lim, Amanda Xinyi (2018)
This paper presents Singapore Undercovered, a communication campaign by four final-year undergraduates from the Wee Kim Wee School of Communication and Information, Nanyang Technological University. The campaign was carried out as a pilot project, aimed at broadening young Singaporeans’ perspectives on modern Singapore culture. Singapore Undercovered targeted secondary school students in Singapore aged 13 to 17, addressing their narrow understanding and appreciation of local culture. Qualitative and quantitative research was carried out to better understand the current sentiments of Singaporean students towards local culture and existing cultural field trips. Our research findings revealed a need to expand the current perceptions of culture to reflect a more-encompassing and modern definition. Hence, field trips to home-grown start-ups and businesses were crafted and executed in four secondary schools, exposing students to concepts of technology and entrepreneurial spirit as part of Singapore’s modern culture. The trips were accompanied by exhibitions held in the four schools. The on-ground engagement, conducted from February to March 2018, was well-received by students, teachers and field trip partners. To conclude our campaign, a closing event will be carried out on 11th April 2018, with MP Baey Yam Keng as Guest-Of-Honour. Post-campaign research, comprising surveys, interviews and focus groups, was carried out to evaluate the campaign’s effectiveness. Thereafter, key achievements and limitations of the campaign were discussed, along with recommendations for the continuation of this campaign in schools across Singapore. Original documents, including campaign collaterals, event photographs and relevant data, have been included in the appendices.